Reflectogram shape deformation in distributed fibre systems in the presence of spontaneous noise in the probe radiation. (December 2021) - Kalmykov, N.I.; Kovalenko, D.A.; Lobach, I.A.; Kablukov, S.I.
Abstract: We report a study of the effect of spontaneous emission-induced noise in probe pulsed radiation on the reflectogram shape deformation in a distributed temperature sensor based on Raman scattering of light. Since the fraction of spontaneous emission in the used erbiumdoped amplifier can reach 50 % of the total power, this leads to deviations of reflectograms in the temperature sensor from the theoretical exponential dependence and, as a result, can yield a temperature measurement error of several degrees. Filtering the radiation with an amplitude modulator makes it possible to reduce these deviations. The influence of spontaneous emission on reflectograms is studied theoretically and experimentally.